2021
DOI: 10.1038/s41467-021-26043-y
|View full text |Cite
|
Sign up to set email alerts
|

Approaching disorder-tolerant semiconducting polymers

Abstract: Doping has been widely used to control the charge carrier concentration in organic semiconductors. However, in conjugated polymers, n-doping is often limited by the tradeoff between doping efficiency and charge carrier mobilities, since dopants often randomly distribute within polymers, leading to significant structural and energetic disorder. Here, we screen a large number of polymer building block combinations and explore the possibility of designing n-type conjugated polymers with good tolerance to dopant-i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
69
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 72 publications
(69 citation statements)
references
References 46 publications
0
69
0
Order By: Relevance
“…32–34 To quantify torsional conformations and their relative contribution to the overall structural disorder, a planarity index (〈cos 2 θ 〉) was introduced as an empirical parameter. 35,36 We found that the combinations of TzII and thiophene ( θ 1 ) units, thiophene and thiophene ( θ 2 ) units, thiophene and DPP ( θ 3 ) units show high 〈cos 2 θ 1 〉, 〈cos 2 θ 2 〉, and 〈cos 2 θ 3 〉 values of 0.9326, 0.8834, and 0.9272, respectively. This result indicated the high planarization for T-TzII-T-DPP conjugated backbone would be expected owing to its high rotation barrier and low relative energy level of the conformer with the three dihedral angles of around 0°.…”
Section: Resultsmentioning
confidence: 85%
“…32–34 To quantify torsional conformations and their relative contribution to the overall structural disorder, a planarity index (〈cos 2 θ 〉) was introduced as an empirical parameter. 35,36 We found that the combinations of TzII and thiophene ( θ 1 ) units, thiophene and thiophene ( θ 2 ) units, thiophene and DPP ( θ 3 ) units show high 〈cos 2 θ 1 〉, 〈cos 2 θ 2 〉, and 〈cos 2 θ 3 〉 values of 0.9326, 0.8834, and 0.9272, respectively. This result indicated the high planarization for T-TzII-T-DPP conjugated backbone would be expected owing to its high rotation barrier and low relative energy level of the conformer with the three dihedral angles of around 0°.…”
Section: Resultsmentioning
confidence: 85%
“…The other study, by X. Yan et al, designed a series of π-CPs of P(PzDPP-2FT) and P(PzDPP-4F2T) with sufficient intramolecular hydrogen bonds, which promoted the planarization of polymers, as shown in Figure 5. 67 The π-backbone of P(PzDPP-2FT) was disclosed to be zigzag curved by DFT calculations, relative to the pseudo-linear backbone of P(PzDPP-4F2T). Consistent with the guideline put forward by the previous study, the single bond connection in the torsion-susceptible linker of 4F2T led to the less planar structure of P(PzDPP-4F2T) than P(PzDPP-2FT).…”
Section: Electrical Characteristicsmentioning
confidence: 96%
“…41 The significance of the tail state distribution width and slope of the band tail has been confirmed by multiple experimental studies, where a narrower width corresponds to lower energetic disorder along the polymer backbone and higher mobilities. 28,42,43 Additionally, narrower bands in the DOS is a characteristic that could indicate higher mobility as it places charge carriers closer to the vicinity of the more delocalised states at the band edge. 44 The DOS thus provides us with a “checklist” of target features with which we can correlate atomistic features and its features which indicate high charge carrier mobility.…”
Section: Introductionmentioning
confidence: 99%